Evaluation of single and double-locus real-time PCR assays for methicillin-resistant Staphylococcus aureus (MRSA) surveillance - Arielly Haya; Kolman Sara; Paitan Yossi (BMC Research Notes, 2010)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) is a human pathogen, representing an infection control challenge. Conventional MRSA screening takes up to three days, therefore development of rapid detection is essential. Real time-PCR (rt-PCR) is the fastest method fulfilling this task. All currently published or commercially available rt-PCR MRSA assays relay on single or double-locus detection. Double-locus assays are based on simultaneous detection of mecA gene and a S. aureus-specific gene. Such assays cannot be applied on clinical samples, which often contain both coagulase-negative staphylococci (CoNS) and S. aureus, either of which can carry mecA. Single-locus assays are based on detection of the staphylococcal cassette chromosome mec (SCCmec) element and the S. aureus-specific orfX gene, assuming that it is equivalent to mecA detection. Findings Parallel evaluation of several published single and double-locus rt-PCR MRSA assays of 150 pure culture strains, followed by analysis of 460 swab-derived clinical samples which included standard identification, susceptibility testing, followed by PCR detection of staphylococcal suspected isolates and in-PCR mixed bacterial populations analysis indicated the following findings. Pure cultures analysis indicated that one of the single-locus assay had very high prevalence of false positives (Positive predictive value = 77.8%) and was excluded from further analysis. Analysis of 460 swab-derived samples indicated that the second single-locus assay misidentified 16 out of 219 MRSA's and 13 out of 90 methicillin-sensitive S. aureus's (MSSA) were misidentified as MRSA's. The double-locus detection assay misidentified 55 out of 90 MSSA's. 46 MSSA containing samples were misidentified as MRSA and 9 as other than S. aureus ending with low positive predicted value (<85%) and very low specificity (<62%). Conclusion The results indicate that high prevalence of false-positive and false-negative reactions occurs in such assays.